Kampung dolanan Taman Jajar Gumregah: The existence of traditional and movement games to support children's growth and development - Wahyu Dwi Lestari; Hendra Maulana; Praja Firdaus Nuryananda; Dwi Wahyuningtyas; Diana Aqidatun Nisa; Yisti Vita Via (Universitas Muhammadiyah Malang, 2025)
Traditional games are increasingly displaced by gadget‑based play, reducing children’s physical activity and opportunities for character formation in many communities. The objective of this program was to establish a community‑based “Kampung Dolanan” in Jajar Village and to evaluate changes in parents’ understanding of the role of traditional and movement games in child growth and character. The methods used were a six‑month community‑engagement intervention that designed and installed traditional game stations (e.g., congklak, stilts, sack race) and movement stations (suspension bridge, tire tower, rope climbing, miniature rock climbing), complemented by outreach, socialization, and a fun competition; a brief five‑item pre–post questionnaire was administered to attending parents/guardians. The results showed that parents recognizing the link between traditional games and child development increased from 40% to 90%, awareness of character‑building roles rose from 30% to 95%, the perception that traditional games are dangerous decreased from 70% to 10%, the preference to keep children at home with gadgets declined from 75% to 10%, and awareness that traditional games stimulate growth and development rose from 25% to 90%. In conclusion, the program improved parental understanding and strengthened community buy‑in for traditional and movement games, indicating that coupling safe, culturally resonant play facilities with targeted outreach can support children’s growth and character while future work measures behavioral outcomes and sustains facilities through village policies and partnerships.